Labor market institutions and policies in old and new EU members - Riccardo Rovelli (IZA World of Labor, 2024)
Old and new EU member states still adopt quite different labor market institutions and policies: convergence has been partial and limited. Nevertheless, a new agreement is spreading on the importance of well-developed, coordinated institutions, supported by social dialogue, in view of the increasing challenges posed by the macro economy and by the increasing fragmentation of labor markets.
Keywords: 330; labor market institutions; wage coordination; union density; labor market power; social dialogue